2020
DOI: 10.20473/jipk.v12i2.17846
|View full text |Cite
|
Sign up to set email alerts
|

The Numerical Phenetic of Taxonomy Vibrio in Shellfish (Meretrix meretrix) at Edu-Tourism Mangrove Cengkrong Beach Trenggalek

Abstract: HighlightIdentify the Vibrio bacteriaDiversity of shellfish Vibrio bacteria (Meretrix Meretrix)Relationship similarity of Vibrio bacteria with MVSP 3.1 Program produces DendogramAbstract Meretrix meretrix is one type of shellfish that is potential, and economic value, which high animal protein content as well as seafood that is widely consumed in Indonesia. This study aims to determine the diversity and similarity of Vibrio in M. meretrix at eduwisata mangrove Cengkrong Beach, Trenggalek. Isolation and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The scoring results are accumulated for the dendogram construction using the MVSP3.1 software. Generating similarity between species was estimated by Simple Matching Coefficient (SSM) and cluster building was carried out using Eucledian method [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring results are accumulated for the dendogram construction using the MVSP3.1 software. Generating similarity between species was estimated by Simple Matching Coefficient (SSM) and cluster building was carried out using Eucledian method [9].…”
Section: Methodsmentioning
confidence: 99%
“…The praying mantis (Hierodula vitrea) has greater abundance and diversity in the tropics and macronesia. The number of praying mantis species is estimated to be more than 2,300 species [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…: green bacteria colonies and yellowish bacteria (Figure 1). The green color of the colonies indicates the nature of vibrio, which cannot ferment sucrose, while the yellow colonies can ferment sucrose and lower the pH in TCBSA media (Ihsan & Retnaningrum, 2017). Further, Rahmanto et al (2014) identified the type of Vibrio from the color of the colonies it forms.…”
Section: Vibrio Sp Bacteriamentioning
confidence: 99%
“…Further classification and characterization of Enterobacteriaceae can be done by numerical-phenetic characterization based on biochemical and phenotypic properties of strains Britto et al 2018). These biochemical and protein properties coffering at least 50 parameters can be used to construct a dendrogram for more precise identification of bacteria (Ihsan and Retnaningrum 2020).…”
Section: Introductionmentioning
confidence: 99%